2020
DOI: 10.1098/rsob.190274
|View full text |Cite
|
Sign up to set email alerts
|

The potential and challenges of patient-derived organoids in guiding the multimodality treatment of upper gastrointestinal malignancies

Abstract: The incidence of adenocarcinoma at the gastrooesophageal junction increased over the last years. Curative treatment for patients with upper gastrointestinal (UGI) malignancies, such as oesophageal and gastric tumours, is challenging and requires a multidisciplinary approach. Radical surgical resection with complete lymphadenectomy is the cornerstone of UGI cancer treatment. Combined with peri-operative treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…For example, a protocol to grow and maintain organoids derived from human endometrial cancer was recently described by Boretto et al [ 110 ]. This publication is a good example of how to create organoids from cells of cancer patient biopsies and highlights the potential of these in vitro models to develop personalized medicine [ 109 , 110 , 111 , 112 , 113 ]. Recently, Driehuis et al reported an overview of the different protocols for the generation of organoids from various cancer types, including a protocol to test the sensitivity of patient-derived organoids to specific cancer therapies [ 114 ].…”
Section: From 2d To 3d Cancer Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a protocol to grow and maintain organoids derived from human endometrial cancer was recently described by Boretto et al [ 110 ]. This publication is a good example of how to create organoids from cells of cancer patient biopsies and highlights the potential of these in vitro models to develop personalized medicine [ 109 , 110 , 111 , 112 , 113 ]. Recently, Driehuis et al reported an overview of the different protocols for the generation of organoids from various cancer types, including a protocol to test the sensitivity of patient-derived organoids to specific cancer therapies [ 114 ].…”
Section: From 2d To 3d Cancer Modelsmentioning
confidence: 99%
“…The patient specificity makes organoids extremely popular in personalized medicine and drug screening tests. Immense breakthroughs have already been made by using these models in treatment response prediction tests [ 112 , 115 , 116 , 117 ]. Cancer organoids (or tumoroids), recapitulate the in vivo tissue heterogeneity, including the presence of a stem cell population [ 118 ].…”
Section: From 2d To 3d Cancer Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond numerous biological challenges 6,7 , the organoid cultures also pose technological challenges, in terms of cell culture methods, characterization of transcriptomics, and imaging. In vivo organ development occurs in a biological environment that results in a highly stereotypical self-organization of cell arrangements.…”
Section: Introductionmentioning
confidence: 99%
“…By establishing models, which resemble the patient’s situation more closely, many research groups hope that the adequate therapy for the individual patient can be determined with a higher probability. Over the past years, patient-derived organoids (PDOs) from many different tumor types have been established and gained interest as a tool for drug screening ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%